PEMUTUSAN HUBUNGAN KERJA AKIBAT TINDAKAN PERSELINGKUHAN ANTAR PEKERJA SEKANTOR - Weny Putri Amelia; Sulastri (2021)
Termination of employment, for this reason, is usually carried out unilaterally. This research raises the problem: first, can the act of adultery between office workers be used as an excuse by employers to terminate the employment relationship? Second, what is the legal protection for workers who have been dismissed for reasons of infidelity? This research uses normative legal research methods. This research concludes first, termination of employment for reasons of infidelity can be done on the condition that the prohibited reasons are specifically written in the Work Agreement or Collective Labor Agreement / Company Regulation, because if it refers to Law No. 13 of 2003 does not contain specific rules regarding termination of employment for reasons of infidelity so it is returned to the existing rules in the work agreement or collective labor agreement/company regulations. Second, related to the legal protection of workers who have been dismissed on the grounds of infidelity. Workers who have been terminated, in this case, are terminated from work for reasons of infidelity, are entitled to legal protection based on the prevailing laws. It provides legal protection and ensures that the rights of workers who have been terminated from work are also fulfilled.